Proposed new interior design of X-Box Flagship Retail Centre for Game on.com at Mid Valley Mega Mall,Third Floor Kuala Lumpur / Nik Muhammad Ziyan Nik Mohd Yusoff - Nik Mohd Yusoff, Nik Muhammad Ziyan (Faculty of Architecture, Planning and Surveying, 2011)
The proposed of X Box Flagship is one of the project that created for Game on.com the gaming shop centre. The reasons of proposed this project is,to show the product of X Box brand and others gadget of X Box around the world. And this project also wants to create one of a big space for gamers and all X Box gadget lovers complete with the gaming expirience inside. In this project our mission is to show to the world that X Box gadget is not only for gamers but it for all of us, and with X Box we can feel the different of gaming experience inside the interior space. This proposed project is the first of gamers flagship in Malaysia.it also will produced one of gamers space with high-tec and others special features inside the space. This gamers flagship is also a retail shop for X Box lovers in Malaysia,it will sell all X Box latest gadget, it will help all X Box lover to get all the letest games or gadget here. My project is to focus more on gaming experience for all gamers in malaysia.so that if they get into the space they can feel the different of gaming world inside. This proposed project is located at Mid Valley Mega Mall Third Floor near the others competitors like Toys For Us,Toy City, Sony Centre.Mega kidz and Star Game. This project will be success because the X Box brand is one of the indoor famous entertainment in Malaysia.